MYKAKIPOTA BERBASIS AUGMENTED REALITY UNTUK PRAKTIK PENDIDIKAN SENI TARI SISWA SEKOLAH DASAR - Wardhana, Wisnu; Ratnaningrum, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The objective of this research is to develop a range of learning resources to enhance student engagement and improve learning outcomes. In this research, we have employed a research and development (R&D) method, drawing upon the well-established model put forth by Borg and Gall.. The data analysis techniques employed were the normality test, the Wilcoxon signed-rank test, and the NGain test. The results of the myKAKIPOTA media feasibility test on media experts indicated that the criteria were highly feasible, with an average value of 95%. The results of the material experts' validation process yielded very feasible criteria with an average value of 87.5%. Furthermore, the product trial results indicated an 87.7% (very good) rating from students and an 89.5% (very good) rating from class teachers. The effectiveness of the myKAKIPOTA media is demonstrated by the Wilcoxon signed test, which indicates a notable impact of utilizing myKAKIPOTA media. The N-Gain test yielded a result of 0.70 which can be concluded to indicate that the KAKIPOTA media that has been developed is declared feasible and effective in learning dance on floor pattern material.